Implementasi Kebijakan Pengisian Jabatan Pimpinan Tinggi Pratama Melalui Seleksi Terbuka Di Lingkungan Pemerintah Kota Palangka Raya - Yuririn Richi; Bulkani Bulkani; Mita Sari (Pencerah Publik, 2020)
This research departs from the phenomenons as a new system the policy of implementation of open selection within the palangka raya city government has been responded to by varios civil servant especially in Palangka Raya government environment and civil servants who register as participants does not match the exected amount so that an extention of the registratration period. In this study using a qualitative approach. The research data was obtained from direct observations, interviews and collecting documents and using triangulation of data sources and theory triangulation. Based on the result of research that the policy implementation of primary leader position through open selection in the Palangka Raya city government environment has been going well but not yet optimal. The low interest of civil servant to participate in open selection is because there is an assumption that open selection is only a formality. The constraints faced are the tendency factor, whish is the attitudes and interest of the civil servant who are still lacking and the resource factor, which is inadequate facilitieas so that it entails a large cost for building rent. The aouthor suggest that the city government of Palangka Raya should be able to actively and consistenly as well as maintain commitments so that in the future the implementation of open selection can gain the trust and interest of the sivil servants, continue to improve in the provision and improvements of facilies such as building, meeting rooms, computers and equipment, using the assessor who has been accredited by the state personnel agency and for the competency test stage can take advantage of the results of the talent pool conducted by the state personnel board competency assessment center.